2017
DOI: 10.1539/joh.15-0264-oa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coke oven emissions and benzo[a]pyrene on blood pressure and electrocardiogram in coke oven workers

Abstract: Objective: To evaluate the effects of occupational exposures to coke oven emissions (COEs) and benzo[a]pyrene (B[a]P) on the prevalence of hypertension and abnormal electrocardiogram (ECG) in coke oven workers.Methods: We included 880 coke oven workers and 710 oxygen employees in the exposed and control groups, respectively. Blood pressure (BP), ECG, blood lipid levels, and glucose levels of all subjects were measured. COE and B[a]P concentrations at the bottom, side, and top of the oven and control plants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Coke oven workers are highly exposed to PAHs, and studies have associated coke oven emission to hypertension and abnormal electrocardiography [142144]. Furthermore, the levels of 2-hydroxyphenanthrene, 3-hydroxybenzo[ a ]pyrene, and 3-hydroxy-benzo[ a ]anthracene were positively associated with diastolic blood pressure in chimney sweepers [145].…”
Section: The Role Of Organic Chemicals and Pah In Mediating Cvdmentioning
confidence: 99%
“…Coke oven workers are highly exposed to PAHs, and studies have associated coke oven emission to hypertension and abnormal electrocardiography [142144]. Furthermore, the levels of 2-hydroxyphenanthrene, 3-hydroxybenzo[ a ]pyrene, and 3-hydroxy-benzo[ a ]anthracene were positively associated with diastolic blood pressure in chimney sweepers [145].…”
Section: The Role Of Organic Chemicals and Pah In Mediating Cvdmentioning
confidence: 99%
“…Levels of urinary PAH biomarkers have been associated with CVD in US adults [ 12 ], and a link between exposure to PAHs and pre-hypertension has been reported in children [ 13 ]. Furthermore, benzo[ a ]pyrene (B[ a ]P), often used as an indicator of PAHs [ 14 ], was associated with blood pressure elevation in coke oven workers [ 15 ]. In line with studies indicating PAHs adhered to inhaled particles may diffuse into the bloodstream [ 14 , 16 , 17 ], recent findings from our laboratory suggest that lipophilic DEP-OC may penetrate the epithelial layer of a 3D tri-culture mimicking the alveolar barrier and affect endothelial cells, triggering pro-inflammatory responses [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coke oven workers and chimney sweeps are exposed to high levels of PAHs. Coke oven emissions are associated with hypertension and abnormal electrocardiographic parameters 37 . One study showed that PAH metabolites including 2-hydroxyphenanthrene, 3-hydroxybenzo[a]pyrene, and 3-hydroxy-benzo[a]anthracene are associated with increased diastolic blood pressure in chimney sweeps 38 .…”
Section: Discussionmentioning
confidence: 99%